Post-activation potentiation: Is there an optimal training volume and intensity to induce improvements in vertical jump ability in highly-trained subjects? - Kobal, R.; Pereira, L. A.; Kitamura, K.; Paulo, A. C.; Ramos, H. A.; Carmo, E. C.; Roschel, H.; Tricoli, V.; Bishop, C.; Loturco, I. (Journal of Human Kinetics, 2019)
The aim of this study was to compare the acute effects of performing half squats (HSs) with different loading intensities (1, 3, and 5 repetitions maximum [RM], and 60% 1RM) and a different number of sets (1, 2, and 3) on the countermovement jump (CMJ) performance of 18 highly-trained male subjects. Participants were submitted to four experimental conditions (1RM, 3RM, 5RM, and 60% 1RM) in randomized order. The CMJ was assessed before and after each set. Differences in CMJ performance between the distinct experimental conditions and individual responses in CMJ performance induced by the different protocols were analyzed via the magnitude-based inference method. Overall, significant improvements were detected in individual CMJ heights after each activation protocol. It can be concluded that the use of 1 to 3 sets of HSs performed at moderate-to-high loads may be an effective strategy to improve jump performance in highly-trained subjects. Nevertheless, despite the high efficiency of the protocols tested here, coaches and researchers are strongly encouraged to perform individualized assessments within the proposed range of loads and sets, to find optimal and tailored post-activation potentiation protocols.